2011
DOI: 10.1073/pnas.1106344108
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA polymerase editing mutation, Polg D257A , reduces the diabetic phenotype of Akita male mice by suppressing appetite

Abstract: Diabetes and the development of its complications have been associated with mitochondrial DNA (mtDNA) dysfunction, but causal relationships remain undetermined. With the objective of testing whether increased mtDNA mutations exacerbate the diabetic phenotype, we have compared mice heterozygous for the Akita diabetogenic mutation (Akita) with mice homozygous for the D257A mutation in mitochondrial DNA polymerase gamma (Polg) or with mice having both mutations (Polg-Akita). The Polg-D257A protein is defective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The depletion of germ cells in the testes here and elsewhere (1, 2, 20) was associated with a decreased weight of the epididymis (Fig. 1 D ) and a dramatic decline in the number of spermatozoa therein (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…The depletion of germ cells in the testes here and elsewhere (1, 2, 20) was associated with a decreased weight of the epididymis (Fig. 1 D ) and a dramatic decline in the number of spermatozoa therein (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…When crossed with Polg-Akita mice that are associated with hyperglycemia, Polg D257A/D257A /Akita double mutant mice had decreased hyperglycemia. This unexpected finding was attributed to appetite suppression, caused by expression of anorexic genes in the hypothalamus, triggered by a reduced level of testosterone [Fox et al, 2011]. Polg D257A/D257A mice developed cardiomyopathy at 13 to 14 months of age.…”
Section: Dna Polymerase Gamma (Pol C)mentioning
confidence: 99%
“…However, many studies have indicated that mtDNA alteration could be a result of ROS-independent phenomena such as replication errors and failure of the repair mechanisms [73][74][75]. In this context, mice with mtDNA polymerase gamma knock-down (PolgD257A/D275A) have shown somatic mtDNA mutation accumulation and shorter longevity without increasing ROS production [76].…”
Section: Mitochondriamentioning
confidence: 99%